2010
DOI: 10.4113/jom.2010.1087
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of non visual maritime cognitive maps of a blind sailor: a case study

Abstract: Nowadays, thanks to the accessibility of GPS, sighted people widely use electronic charts to navigate through different kinds of environments. In the maritime domain, it has considerably improved the precision of course control. In this domain, blind sailors can not make a compass bearing, however they are able to interact with multimodal electronic charts. Indeed, we conceived SeaTouch, a haptic (tactilekinesthetic) and auditory virtual environment that allows users to perform virtual maritime navigation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Similar results were found among adults and children who were totally blind or had residual vision, but different results were found among children with residual vision and medium cognitive achievement were unable to create a spatial cognitive map (Sá nchez and Lumbreras, 2000). Simonnet et al (2010) found that as a result of getting lost frequently in the egocentric exploration mode, the participant constructed a more precise cognitive map.…”
Section: Research Dimensionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar results were found among adults and children who were totally blind or had residual vision, but different results were found among children with residual vision and medium cognitive achievement were unable to create a spatial cognitive map (Sá nchez and Lumbreras, 2000). Simonnet et al (2010) found that as a result of getting lost frequently in the egocentric exploration mode, the participant constructed a more precise cognitive map.…”
Section: Research Dimensionsupporting
confidence: 65%
“…2 2014 j JOURNAL OF ASSISTIVE TECHNOLOGIES j PAGE 103 needed on how these aspects of the VE affect the user's ability to gather spatial information and apply it in the RS. Simonnet et al (2010) demonstrate that further research is needed to examine if and how the VE's spatial exploration method (allocentric or geocentric representations) influences the user's spatial model (route model or map model), a topic that was less commonly examined and which might have an influence on the user's ultimate ability and outcome in using a VE. Additionally, the research must proceed to examine the real-life scenarios in which this type of O&M aid is most needed, such as outdoor and complex spaces, and examine the user's ability to apply the new spatial knowledge in the RS.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to form a cognitive map of a haptically presented environment has been suggested in earlier research, considering people with a visual impairment as well as sighted people 18 23 . Furthermore, there is a large body of literature that shows the effectiveness of tactile maps to support blind people in wayfinding and orientation 18 , 21 , 24 31 . There are several methods to assess the formation of mental spatial representations 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it might be incumbent on future interfaces to include a haptic component for the surgeons to respond. In a very different domain, an experimental interface, which combines auditory feedback and a forcefeel joystick, allows blind sailors to direct a crew on a sailing vessel in tests off the coast of France (Simonnet et al 2010). Thus, to the extent which spatial interfaces engage the user in the physical environment (Meilinger et al 2008), there should be additional encoding and better memory of the environment.…”
Section: Impact On Spatial Learningmentioning
confidence: 99%